2023
DOI: 10.3390/ijms241210151
|View full text |Cite
|
Sign up to set email alerts
|

Five-Aminolevulinic Acid (5-ALA) Induces Heme Oxygenase-1 and Ameliorates Palmitic Acid-Induced Endoplasmic Reticulum Stress in Renal Tubules

Abstract: Steatosis, or ectopic lipid deposition, is the fundamental pathophysiology of non-alcoholic steatohepatitis and chronic kidney disease. Steatosis in the renal tubule causes endoplasmic reticulum (ER) stress, leading to kidney injury. Thus, ER stress could be a therapeutic target in steatonephropathy. Five-aminolevulinic acid (5-ALA) is a natural product that induces heme oxygenase (HO)-1, which acts as an antioxidant. This study aimed to investigate the therapeutic potential of 5-ALA in lipotoxicity-induced ER… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 45 publications
(59 reference statements)
0
1
0
Order By: Relevance
“…As a critical exogenous risk factor, long-term consumption of HFD will inevitably lead to abnormal elevation of serum FA levels, which are further taken by renal tubules and stored as triglyceride, leading to renal tubular ELD . Emerging studies have shown that renal tubular ELD could cause lipotoxic damage to intrinsic renal tubular cells, following a pathology typified by hyperactivation of intracellular metabolic, oxidative, and inflammatory pathways that could ultimately provoke cell death. , Recently, several bioactive polysaccharides derived from natural products have been shown in evidence-based studies to be beneficial in countering HFD-induced metabolic disorders, including renal tubular ELD, , indicating that prolonged supplementation of such natural polysaccharides may be a beneficial strategy to reduce the risk of renal tubular ELD and CKD. Previously, we reported a homogeneous tea polysaccharide, TPS3A, with a strong potential to ameliorate HFD-exposed lipid metabolism disturbances in ApoE –/– mice .…”
Section: Discussionmentioning
confidence: 99%
“…As a critical exogenous risk factor, long-term consumption of HFD will inevitably lead to abnormal elevation of serum FA levels, which are further taken by renal tubules and stored as triglyceride, leading to renal tubular ELD . Emerging studies have shown that renal tubular ELD could cause lipotoxic damage to intrinsic renal tubular cells, following a pathology typified by hyperactivation of intracellular metabolic, oxidative, and inflammatory pathways that could ultimately provoke cell death. , Recently, several bioactive polysaccharides derived from natural products have been shown in evidence-based studies to be beneficial in countering HFD-induced metabolic disorders, including renal tubular ELD, , indicating that prolonged supplementation of such natural polysaccharides may be a beneficial strategy to reduce the risk of renal tubular ELD and CKD. Previously, we reported a homogeneous tea polysaccharide, TPS3A, with a strong potential to ameliorate HFD-exposed lipid metabolism disturbances in ApoE –/– mice .…”
Section: Discussionmentioning
confidence: 99%